A Comparative Study of Migrant Workers’ Rights in Saudi Arabia and World Cup Host Nations - Mariam bin Ghait (Law and Social Justice in Society, 2026)
This study assesses Saudi Arabia's readiness for the 2034 World Cup by comparing it with Brazil's (2014) and Qatar's (2022) preparations, with a focus on the protection of migrant workers. Using a socio-legal approach, the study examines the relationship between the legal framework and the social practices of migrant workers on the ground; a normative-comparative approach is used to examine labour regulations and reforms related to Kafala in the three countries; and a historical approach traces the evolution of migrant policies before and after the World Cup hosting. The results show that Brazil failed to implement significant reforms despite global scrutiny. At the same time, Qatar successfully implemented structural changes, including the elimination of exit permits, the introduction of a universal minimum wage, a dispute resolution mechanism, and a compensation fund. Saudi Arabia has initiated reforms, including the partial relaxation of the Kafala system, the digitisation of contracts, and the strengthening of the wage protection system; however, protection remains limited to specific sectors. The study concludes that Saudi Arabia needs to expand reforms, strengthen oversight, and enhance its partnership with the ILO to meet international labour standards by 2034.